Transformasi Kompetensi Guru dengan Inovasi Pembelajaran Berkarakter Berbasis Artificial Intelligence di Madrasah Tsanawiyah Nurul Huda Muaro Jambi - Adang Ridwan; Ria Karmila; Sri Hidayati; Harlina Harja; Rian Septiawan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The rapid development of digital technology requires teachers to possess competencies that are relevant to modern learning needs. This necessity underlies the focus of this community service program, namely transforming teacher competencies through character-based learning innovation supported by Artificial Intelligence (AI). The program was conducted at Madrasah Tsanawiyah Nurul Huda Muaro Jambi with the aim of strengthening teachers’ skills in utilizing AI as a tool to support interactive learning while instilling character values in students. The method included socialization, training, and direct mentoring in the practical application of AI-based learning media in the classroom. The results showed significant improvements in teachers’ ability to design technology-based learning materials, a better understanding of integrating character education, and increased motivation to innovate. Furthermore, the program fostered a more engaging learning atmosphere aligned with the needs of the digital generation. Therefore, the transformation of teacher competencies through AI not only enhances teacher professionalism but also plays a crucial role in shaping students with strong character amid technological advancement.